A rare pediatric case of lichen planus pigmentosus with scalp involvement - Barbato, Filomena; Licata, Gaetano; Damiani, Luca; Calandriello, Giovanni; Prisco, Antonio; Di Brizzi, Eugenia Veronica; Giorgio, Caterina Mariarosaria (Dermatology Reports, 2026)
Dear Editor, Lichen planus pigmentosus (LPP) is a chronic inflammatory dermatosis mainly reported in adults from the Indian subcontinent and the Middle East. Pediatric cases are exceedingly rare, and LPP involving the scalp has not been previously described. Given the paucity of literature on childhood LPP, we present a case that broadens the spectrum of clinical presentations of this disease. [...]